Mitigating secondary agency problems: examining the impact of share option compensation for non-executive directors on CEO pay incentives and earnings management - Majoni, Akios (Department of Finance and Tax, 2020)
This thesis investigates the following objectives: first, it analyses trends in share option compensation for NEDs during the pre–King III period (before they were stopped). The idea is to determine whether the decision to stop them was triggered by a significant increase in their use. The trend analysis is extended to observe changes in the use of share options for NEDs over the full sample period. The intention of this sub–objective is to measure the extent of compliance to King III’s requirement to stop the use of share option compensation for NEDs. Second, the study exploits the natural experiment, presented by King III’s requirement to stop the use of share option compensation for NEDs, to investigate the impact of share option compensation for NEDs on monitoring executives. In addition, the study investigates how institutional and blockholder ownership affect the relationship between share option compensation for NEDs and monitoring (to see whether they are substitutes). Both institutional and blockholder owners consist of heterogeneous categories with different monitoring incentives; hence, a further analysis examines the moderating impact of these different categories of stakeholders. To measure the level of monitoring, the study focuses on two of the biggest agency problems in South Africa: design of CEO compensation and levels of earnings management. The study is based on a sample of 110 non–financial companies (55 in the treatment group and 55 in the control group) listed on the Johannesburg Stock Exchange (JSE), South Africa, over the period 2002–2016. The bulk of the data used was hand–collected from annual reports, the rest was sourced from financial databases such as Bloomberg, Iress and DataStream. The difference– in–difference regression analysis is the main methodology used but for comparison purposes, the study also applies the normal Ordinary Least Squares (OLS) regression and fixed effects model. To control for the endogeneity problem, the study is based on a natural experiment, which is dubbed the ‘gold standard’ for addressing endogeneity problems. Addressing the endogeneity problem is key to satisfactorily settling the debate on the effectiveness of equity–based compensation in mitigating secondary agency problems. The results of the trend analysis show that the growth in share option compensation for NEDs was not statistically significant during the pre–King III period. These results rule out the possibility that King III’s recommendation to stop the use of share option compensation for NEDs was driven by an explosion in their use. As expected, after the introduction of King III, the use of share options declined significantly – an indication that companies largely complied with the requirement to stop the use of share options as compensation for NEDs. However, not all companies are compliant; this is not surprising, as King III was based on the ‘apply or explain’ approach. Regarding the impact of share option compensation on monitoring, the results consistently show that removing share option compensation for NEDs does not weaken monitoring; it either improves monitoring, or it has no effect. Based on these findings, it is not worthwhile, for shareholders, to use share option compensation for NEDs. They come at a cost, they dilute the shareholding structure yet removing them does not weaken monitoring. Overall, the results support King III’s recommendation to stop the use of share option compensation for NEDs. The results also show that the presence of institutional and blockholder ownership does not improve monitoring after the removal of share option compensation. Hence, neither of these two stakeholders are a substitute monitoring mechanism for share option compensation for NEDs. This is inconsistent with the substitution-monitoring hypothesis. These findings persist, even after a sub–sample analysis of the two categories of institutional ownership (monitoring and non– monitoring institutional owners). A further analysis of different categories of blockholder ownership shows that family, pension and foreign blockholder are not a substitute monitoring mechanism for NEDs share option compensation. But the results for government blockholders contradict this; they are a substitute for share option compensation when analysing real–activities manipulation. However, for the rest of the settings they are not a substitute monitoring mechanism. This confirms the view that different blockholders have different incentives to monitor management, which affects organisational outcomes. The study makes the following contributions: (i) It contributes to the literature by addressing the endogeneity problem using a natural experiment. (ii) The study focuses on a unique institutional context, largely ignored by prior studies on this subject. (iii) The study contributes to the crafting of future corporate governance principles in South Africa and the rest of world, specifically on the design of incentive compensation for NEDs. (iv) By investigating the interaction effects of institutional/blockholder ownership and their different categories, the study provides evidence for the substitution-monitoring hypothesis in South Africa. (v) On the use of share option compensation for NEDs, this study contributes to the literature by showing its impact on mitigating agency problems specifically related to the design of CEO pay incentives.